2023
DOI: 10.3390/ijms241512387
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Transcriptomic and Metabolomic Analyses Uncover the Differential Mechanism in Saline–Alkaline Tolerance between Indica and Japonica Rice at the Seedling Stage

Abstract: Saline–alkaline stress is one of the major damages that severely affects rice (Oryza sativa L.) growth and grain yield; however, the mechanism of the tolerance remains largely unknown in rice. Herein, we comparatively investigated the transcriptome and metabolome of two contrasting rice subspecies genotypes, Luohui 9 (abbreviation for Chao2R under study, O. sativa ssp. indica, saline–alkaline-sensitive) and RPY geng (O. sativa ssp. japonica, saline–alkaline-tolerant), to identify the main pathways and importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 123 publications
0
3
0
Order By: Relevance
“…Transcriptome studies analyzing the ten most resistant and ten most susceptible individuals demonstrated that overexpression of the WAK91 gene improves rice resistance to rice blast, and through the 3000 Rice Genome Project and publicly available genomic data, it was determined that the resistance genes in the WAK91 SNP mutant appeared to be ancestrally inherited, and it was concluded that the WAK91 gene is a candidate for improved resistance to the leaf blight gene [55]. Under salt-alkali stress conditions, a comparative analysis of the transcriptomes of a salt-alkali-tolerant subspecies (RPY Geng) and a relatively sensitive subspecies (Luohui 9) of rice revealed the specific upregulation of multiple genes associated with salt-alkali tolerance in RPY Geng [56]. To understand how rice responds to various abiotic stresses, the transcriptome of IAC1131 rice related to interactions with these stresses was analyzed after various ABA pretreatments [57].…”
Section: Functional Gene Mining For Transcriptome Servicesmentioning
confidence: 99%
“…Transcriptome studies analyzing the ten most resistant and ten most susceptible individuals demonstrated that overexpression of the WAK91 gene improves rice resistance to rice blast, and through the 3000 Rice Genome Project and publicly available genomic data, it was determined that the resistance genes in the WAK91 SNP mutant appeared to be ancestrally inherited, and it was concluded that the WAK91 gene is a candidate for improved resistance to the leaf blight gene [55]. Under salt-alkali stress conditions, a comparative analysis of the transcriptomes of a salt-alkali-tolerant subspecies (RPY Geng) and a relatively sensitive subspecies (Luohui 9) of rice revealed the specific upregulation of multiple genes associated with salt-alkali tolerance in RPY Geng [56]. To understand how rice responds to various abiotic stresses, the transcriptome of IAC1131 rice related to interactions with these stresses was analyzed after various ABA pretreatments [57].…”
Section: Functional Gene Mining For Transcriptome Servicesmentioning
confidence: 99%
“…The former consists of pathogenic microorganisms (fungi, bacteria, and nematodes), insects, and herbivores, as well as nutrient deficiency, extreme temperature, salinity, drought, floods, etc. To survive, plants have evolved sophisticated coping mechanisms to perceive stressful stimuli and activate the necessary cellular responses, including the activation of various kinase cascades [ 1 ], transcriptional reprogramming [ 2 ], reactive oxygen species (ROS) production [ 3 ], and the accumulation of defense-related hormones [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…IAC1131 is a drought-tolerant upland rice cultivar that has been previously shown to be more drought tolerant [16,17], and more tolerant to combined drought, salt, and temperature stress, than Nipponbare, which is a lowland rice that is sensitive to drought and heat stress [3]. Previous studies investigating plant stress responses at the transcriptome level are typically focused on one stress at a time; examples include the transcriptomic characterisation of salt tolerance in germinating rice [18], drought tolerance in rice [19], and salinity-alkalinity tolerance in rice seedlings [20]. In contrast, in this analysis, we analysed the rice transcriptome to explore how rice regulates responses to multiple abiotic stresses imposed simultaneously with or without prior ABA application.…”
Section: Introductionmentioning
confidence: 99%